The impact of metal complex lipids on viscosity and curvature of hybrid liposomes. Issue 99 (29th November 2017) - Ohtani, Ryo; Tokita, Tsukasa; Takaya, Tomohisa; Iwata, Koichi; Kinoshita, Masanao; Matsumori, Nobuaki; Nakamura, Masaaki; Lindoy, Leonard F.; Hayami, Shinya
Abstract : Organic–inorganic hybrid liposomes exhibit stronger interaction between heads but weaker interaction between alkyl chains than occurs in pristine liposomes. Abstract : A morphology transformation of hybrid liposomes was shown to occur from spherical vesicles to tubular micelles when increasing the ratio of the metal complex lipid present. Phase transition temperatures increased while viscosities decreased, indicating that the hybrids exhibit stronger interaction between heads but weaker interaction between alkyl chains than occurs in pristine liposomes.